2014
DOI: 10.1017/jfm.2014.151
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic turbulent drag reduction as a function of surface grating parameters

Abstract: Despite the confirmation of slip flows and successful drag reduction in small-scaled laminar flows, the full impact of superhydrophobic (SHPo) drag reduction remained questionable because of the sporadic and inconsistent experimental results in turbulent flows. Here we report a systematic set of bias-free reduction data obtained by measuring the skin-friction drags on a SHPo surface and a smooth surface at the same time and location in a turbulent boundary layer flow. Each monolithic sample consists of a SHPo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
141
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 37 publications
(11 reference statements)
7
141
0
1
Order By: Relevance
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014). However, an experimental study using a random-structured SHPo surface has reported that at high Re numbers the plastron was found depleted and drag reduction vanished (Aljallis et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014). However, an experimental study using a random-structured SHPo surface has reported that at high Re numbers the plastron was found depleted and drag reduction vanished (Aljallis et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This explains why several experiments have reported that the greatest drag reduction was achieved with either long gratings (16,42) or microposts or random textures having large gas fraction (up to 99%) (8,12). Some of the largest slip lengths were achieved with annular gratings in a circular rheometer (12).…”
Section: Pressure-relaxation Experiments For Surfactant Effectmentioning
confidence: 99%
“…In turbulent flows (such as in ref. 16) mixing is expected to enhance surfactant fluxes, potentially inducing a qualitative change in Marangoni stress. To enable general predictions, it would be important to extend existing effective slip models (27,29,34) to include surfactant.…”
Section: Pressure-relaxation Experiments For Surfactant Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations of turbulent channel flows indicate that the shear-free liquid-vapor interface can reduce skin friction by introducing an effective slip velocity in the viscous sublayer [14,15], and by the suppression of turbulent flow structures in the near-wall region [16]. While recent experimental studies report varying amounts of drag reduction in turbulent flows using SH surfaces [17][18][19], there are inconsistencies in the magnitude of observed drag reduction across studies, and its dependence on the slip length, surface characteristics, and Reynolds number in turbulent flow remain unclear.In this Letter, we demonstrate sustained reduction in frictional drag in turbulent Taylor-Couette (TC) flows by applying a polymeric SH coating to the inner rotor. The extent of drag reduction DR ¼ 100 × ðT flat − T SH Þ=T flat based on the inner rotor torque T , steadily increases with Re up to 22% at Re ¼ 80 000.…”
mentioning
confidence: 99%